ICD-11 Paraphilic Disorders: A South African Analysis of Its Utility in the Medico-Legal Context - Artz, Lillian; Swanepoel, Magdaleen; Nagdee, Mohammed; Combrinck, Helene; Kaliski, Sean; Stein, Dan J; Butterworth, J (Journal of sexual medicine, 2021)
In an effort to improve the clinical utility of the ICD-10, the WHO Working Group on the Classification of Sexual Disorders and Sexual Health recommended a new classification of Paraphilic Disorders in the ICD-11 to replace the ICD-10 section on Disorders of Sexual Preference. The proposed classification may have different implications for different countries. To examine South African national laws and policies, within which Paraphilic Disorders are encountered, and to assess the implications of the new classification. A South African working group - representing experts within the disciplines of criminal law, psychiatry, psychology, public health, and criminology - reviewed: (i) national laws affected by reclassification, (ii) current practices in the psycho-legal assessment of sexual offenders, (iii) the implications of the reclassification for assessment and decision-making in forensic practice and other health settings, (iv) specific implications of the reclassification for diagnosis, and (v) implications of the reclassification as it relates to the demographic and sociocultural context of South Africa. As a rule, South African courts do not accept the existence of a Paraphilic Disorder on its own to be sufficient grounds to absolve any defendant from criminal responsibility though defence. Nevertheless, a diagnosis such as coercive sexual sadism disorder runs the risk of medicalization of criminal behavior with inappropriate use to mitigate sentences. The ICD-11 approach is clinically useful in emphasizing that a broad range of sexual behavior fall under the rubric of healthy sexual behavior, but also that compulsive sexual behavior can be pathological. This analysis was conducted by an interdisciplinary expert group, aligning international forensic mental health and national legal constructs in a low-middle income country (LMIC). The analysis is limited by its reliance on expert opinion rather than empirical data. It is recommended that the ICD-11 includes a cautionary statement for forensic use, highlighting the fact that the mere inclusion of a diagnosis in the ICD-11 does not necessarily have forensic relevance. Artz L, Swanepoel M, Nagdee M, et al. ICD-11 Paraphilic Disorders: A South African Analysis of Its Utility in the Medico-Legal Context. J Sex Med 2021;18:526-538.